PENILAIAN KINERJA LAPORAN REALISASI ANGGARAN PADA DINAS KETAHANAN PANGAN DAN PERIKANAN KABUPATEN TANAH LAUT - Yuli Fitriyani; Tia Febrianti (Jurnal Riset Akuntansi Politala, 2020)
The Budget Realization Report (LRA) is a report published by the local government providing very important and useful information for assessing regional financial performance. LRA is one of the financial reporting entities that are responsible for regional finances. Based on the Budget Realization Report the user or reader of this research report is to find out and analyze the performance of the budget realization report, which includes information about the regional revenue expenditure budget. The analytical method used in this research is a quantitative descriptive method, using the calculation of the effectiveness ratio analysis on Regional Original Income which shows the average 2017 to 2019 budget ratio ineffective performance levels of 34.89%, the efficiency ratio in Regional Expenditures which shows that the overall average in 2017 to 2019 has the criteria of being quite efficient at 85.70%.